APROVEITAMENTO ENERGÉTICO DE BIOMASSA RESIDUAL DE FÁBRICA DE PAPEL-CARTÃO - Ferreira, Italo Tadeu Machado (2015)
One of the biggest problems of the pulp and paper industry is the disposal of solid waste in landfills, since available areas are increasingly scarce, besides the environmental impact with the disposal. On the other hand, the aim is to increase the sustainability of manufacturing processes with increased use of renewable energy inputs, like cellulosic biomass. The goal of this study is to evaluate the energy production potential of cellulosic residues from paperboard mill (fiber sludge from wastewater treatment plant - WWTP, fibers and lint from the production of mechanical wood pulp), in the combustion mixture with wood chips and barks, conventionally used in steam generation. The calorific value of the conventional fuel; wood chips and barks and the cellulosic residues; fibers and wood lint, WWTP sludge and boiler ash were estimated by correlation based on immediate and elemental analyzes of these materials, in order to perform the mass and heat balance of the boiler. The assessment indicated that the amount of energy released in the boiler chimney exhaust gases is sufficient to dry the WWTP sludge, reducing its initial moisture content of 55% to 20% and to dry wood fibers and lint, reducing its moisture 80% to 20%. The drying of the residues in the biomass dryer, can increase the calorific value of WWTP sludge by 55% and increase fiber and lint net heat value by 88%, making possible to burn the dried residues mixed with biomass (wood chips and bark) currently used in the mill boiler. The balance with the introduction of dried residues; 1.5% of fibers and lint and 6.5% of WWTP sludge, in combustion mixed with 89.8% of wood chips and 2.4% of wood bark, indicated that it is possible to reduce 411 tons of wood chips and bark per month. A cost-benefit assessment of available technical alternatives was done, in order to compare the economic feasibility of each possibility. The study indicated that there are alternatives for energy utilization of cellulosic residues from the paperboard mill.